REVITALIZING SOCIAL SANCTIONS OF CUSTOMARY LAW TO ERODE PERMISSIVISM TOWARD CORRUPT BEHAVIOR IN SOCIETY - Firman Freaddy Busroh (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTCorruption is still common in Indonesia. The existence of permissive culture in Indonesian society has caused corruption to continue to flourish and difficult to eradicate. Many cases of corruption have been brought to trial, but it is still unable reduce the level of corruption. Permissive culture (or also known as permissivism) is still often encountered in everyday life, such as granting bribes for administration, from office to religious affairs, such as marriage. The development of this permissive culture is due to the advancement of the times and the increasing lifestyle of hedonism in society which result in the community being consumptive. Unwittingly, the permissive culture has permitted corrupt behavior to occur. Corruption is an act that cannot be justified in any aspect. Corruption is detrimental to the State's finances which has an impact on the waiver of public interest. In addition, corruption also has a negative impact on various fields. So, corruption is an unforgivable act. Therefore, it is necessary to revitalize social sanction in combating the culture of corruption. Indonesia, as a legal laboratory, has various kinds of customary law. Customary law in Indonesia has traditional religious characteristics that use religious and cultural approaches. Some areas in Indonesia that still uphold the value of religion and customs can be used as a foundation to eradicate permissivism of corrupt behavior. In religion and custom there are social sanctions that can cause the feelings of shame for the perpetrators of corruption. Such social sanctions include exclusion, expulsion from a territory, or even the removal of a customary title. The revitalization of social sanctions could be part of a strategy for eradicating corruption in Indonesia.